Design of bandwidth enhancement circular polarisation microstrip antenna loaded with sunflower‐shaped metasurface - Xiumei Shen; Chuanyun Zhang; Yingzeng Yin; Xiangjiang Zhong (IET Microwaves, Antennas & Propagation)
Abstract A circular polarised (CP) microstrip antenna loaded with sunflower‐shaped metasurface (SSM) to enhance the bandwidth using characteristic mode analysis is proposed in this communication. The SSM, divided into inner and outer parts by a ring, consists of equally spaced sectors of equal angles. In this design, the coupled corner‐truncated microstrip antenna with a slot in the centre is employed to obtain CP radiation by exciting two orthogonal modes, which have a 90° phase difference. Meanwhile, it demonstrates that the SSM structure significantly expands the operational bandwidth and exhibits a stable radiation pattern at high frequencies. Simulation and measurement results confirm that this SSM antenna achieves a wide operating bandwidth of 64.3% (4.5–8.76 GHz) and a 3‐dB axial ratio bandwidth of 30.6% (4.7–6.4 GHz), while maintaining a compact profile of 0.68 × 0.68 × 0 0.08 λ03.